2004
DOI: 10.1634/stemcells.2004-0058
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mesenchymal Stem Cells of Fetal or Maternal Origin from Human Placenta

Abstract: Recently we reported that second‐trimester amniotic fluid (AF) is an abundant source of fetal mesenchymal stem cells (MSCs). In this study, we analyze the origin of these MSCs and the presence of MSCs in human‐term AF. In addition, different parts of the human placenta were studied for the presence of either fetal or maternal MSCs. We compared the phenotype and growth characteristics of MSCs derived from AF and placenta. Cells from human second‐trimester (mean gestational age, 19+2 [standard deviation, ± 1+3] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
413
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,003 publications
(440 citation statements)
references
References 21 publications
14
413
0
3
Order By: Relevance
“…Our in vitro differentiation studies support the findings already reported in humans (In 't Anker et al 2004, De Coppi et al 2007) and in equine species (Lange-Consiglio et al 2012): cells isolated from the amniotic epithelial portion, as well as those obtained from the AF, show high plasticity, being able to differentiate into multiple germ layers (mesoderm and ectoderm). In particular, according to data obtained from human amniotic epithelial cells (Miki et al 2005(Miki et al , 2007a, we prove the ability of bovine amnion-derived cells to undergo astrocyte differentiation, as demonstrated by GFAP expression following neurogenic induction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our in vitro differentiation studies support the findings already reported in humans (In 't Anker et al 2004, De Coppi et al 2007) and in equine species (Lange-Consiglio et al 2012): cells isolated from the amniotic epithelial portion, as well as those obtained from the AF, show high plasticity, being able to differentiate into multiple germ layers (mesoderm and ectoderm). In particular, according to data obtained from human amniotic epithelial cells (Miki et al 2005(Miki et al , 2007a, we prove the ability of bovine amnion-derived cells to undergo astrocyte differentiation, as demonstrated by GFAP expression following neurogenic induction.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, MSCs obtained from human amnion have been shown to retain immunomodulatory properties as well as to strongly inhibit T lymphocyte proliferation and to survive when transplanted in immunocompetent animals without inducing any tumorigenic effect in vivo (Avila et al 2001, Kubo et al 2001, Sankar & Muthusamy 2003, Yuge et al 2004. As amnion-derived progenitor cells, MSCs from AF (AF-MSCs) are thought to be in an intermediate stage between embryonic stem cells and lineage-restricted adult stem cells (In 't Anker et al 2004, Delo et al 2006, De Coppi et al 2007, Sessarego et al 2008, Gucciardo et al 2009), originating from several fetal tissues, including skin, digestive, respiratory, and urinary systems (Prusa & Hengstschlager 2002, You et al 2009, Da Sacco et al 2010. AF-MSCs are known to play a role in preventing rejection of the fetus and are thought to have low immunogenicity (Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After these treatments, AFCs gave rise to adipocytes and osteoblasts, when fibroblasts were the predominant cell population. In this regard, it has been reported [10,12,13] that amniotic fluid mesenchymal stem cells display a multilineage differentiation potential into fibroblasts, adipocytes and osteocytes. We suggest that the limited differentiation potential towards mesenchymal lineages that we found in our AFC cultures could be due to the cell heterogeneity with high percentage of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic epithelial cells obtained from cesarean sections have been shown to express markers for neuronal, glial and progenitor cells and to differentiate into neuron-like cells in the ischemic brain of adult rats [7][8][9]. Moreover, there is evidence that amniotic fluid contains fetal mesenchymal stem cells with a multilineage differentiation potential [10][11][12][13]. In this study we extensively characterized unselected amniotic cells and tested their multilineage differentiation capacity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of easy means of isolating and expanding these cells ex-vivo (bone marrow, 15,16 adipose tissue, 16,17 placenta, 18 peripheral blood, 19 and others) also makes MSCs useful cells for therapeutic approaches to supplementing tissue regeneration ( Table 2). Additionally, these cells have been shown to have notable immunomodulatory effects on the surrounding environment following transplantation, [29][30][31][32] and can support native cells with the secretion of a variety of pro-survival and pro-migratory cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%